Improving hydrogen production by pH adjustment in pressurized gas fermentation. (February 2022) - Park, Gwon Woo; Moon, Myounghoon; Park, Jeong-Ho; Jo, Jae-Hwan; Kim, Hyouck Ju; Lee, Jae Yong; Lee, Hyun Sook; Lee, Joon-pyo; Lee, Sangmin; Lee, Soo Youn; Lee, Jiye; Na, Jeong-Geol; et al.
Graphical abstract: Highlights: Microbial culture in the pressurized bubble column reactor. Real-time pH monitoring for a high pressure and temperature gas fermentation. The H2 gas productivity was improved by controlling pH after pressurization. Target (H2 ) productivity in a pressurized bubble column comparable to that of CSTR. Abstract: Gas fermentation utilizes syngas converted from biomass or waste as feedstock. A bubble column reactor for pressurizing was designed to increase the mass transfer rate between gas and liquid, and reduce energy consumption by medium agitation. Thermococcus onnurineus, a hydrogenic CO-oxidizer, was cultured initially under ambient pressure with the initial inlet gas composition; 60% CO and 40% N2 . The maximum H2 productivity was 363 mmol/l/h, without pH adjustment. When additional pressure was applied, the pH rapidly declined; this may be attributed to the increased CO2 solubility under pressure. By controlling pH, H2 productivity increased up to 450 mmol/l/h; which is comparable to the previously reported H2 productivity in a continuous stirred tank reactor. The results may suggest energy saving potentials of bubble column reactors in gas fermentation. This finding may be applied to other gas fermentation processes, as syngas itself contains CO2 and many microbial processes also release CO2 .